Proceedings of the 14th ACM International Conference on Information and Knowledge Management 2005
DOI: 10.1145/1099554.1099561
|View full text |Cite
|
Sign up to set email alerts
|

Generalized contextualization method for XML information retrieval

Abstract: A general re-weighting method, called contextualization, for more efficient element ranking in XML retrieval is introduced. Reweighting is based on the idea of using the ancestors of an element as a context: if the element appears in a good contextgood interpreted as probability of relevance -its weight is increased in relevance scoring; if the element appears in a bad context, its weight is decreased. The formal presentation of contextualization is given in a general XML representation and manipulation frame,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 11 publications
(13 reference statements)
2
31
0
Order By: Relevance
“…Until recently, the importance of contextualization (based on hierarchical relationships of element) has been studied in several settings [1,2,4,19,22,23,25]. Even in a schemaagnostic environment, it has been found that by contextualizing the scores of the surrounding components, such as, parents, ancestors or siblings in the scoring function of the element itself, the overall precision and recall of the focused retrieval system improves [4].…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, the importance of contextualization (based on hierarchical relationships of element) has been studied in several settings [1,2,4,19,22,23,25]. Even in a schemaagnostic environment, it has been found that by contextualizing the scores of the surrounding components, such as, parents, ancestors or siblings in the scoring function of the element itself, the overall precision and recall of the focused retrieval system improves [4].…”
Section: Introductionmentioning
confidence: 99%
“…[Arvola et al, 2005a] and [Arvola et al, 2005b] introduce a new re-weighting method called Contextualization. In this model, the ancestors of an element are considered to be its context.…”
Section: Resultsmentioning
confidence: 99%
“…In [Arvola et al, 2005a], the weighting scheme is based on the probabilistic retrieval framework BM25 [Robertson et al, 1992]:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the parent/child navigation step "/" was considered particularly problematic as it was open to misinterpretation by assessors 3 , and hence was dropped. Also, all result elements must have at least one about() function.…”
Section: Path-based Queriesmentioning
confidence: 99%